114k views
0 votes
How was this answered? i don't know how, pls. help​

How was this answered? i don't know how, pls. help​-example-1
User Kpp
by
5.3k points

1 Answer

6 votes

Answer:

see explanation

Explanation:

Using
√(-1) = i, then i² = (
√(-1) )² = - 1

and i³ = i² × i = - 1 × i = - i

also


i^(4) = i² × i² = - 1 × - 1 = 1

We can surmise that i raised to any multiple of 4 will equal 1

Given


i^(35) ( note 35 = 32 + 3 and 32 is a multiple of 4 ), thus

=
i^(32+3)

= 1 × i³ = - i

User Dan Herman
by
5.4k points